2014
DOI: 10.1590/0103-6440201302254
|View full text |Cite
|
Sign up to set email alerts
|

Cryosurgery as an Effective Alternative for Treatment of Oral Lesions in Children

Abstract: Children can exhibit a wide variety of oral pathologies, such as oral lesions, bone lesions, tumors, cysts and cutaneous lesions. Different techniques have been described for the treatment of these lesions, but all of them are invasive. This paper presents a series of cases that demonstrate the clinical efficacy of cryosurgery as an alternative to invasive surgical treatments of the most common oral lesions in children. This technique has been well tolerated by patients due to the absence of anesthesia, rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
(27 reference statements)
0
11
0
1
Order By: Relevance
“…Other direct effects include degradation and inhibition of enzymes, protein damage, and the formation of cellular vacuoles leading to cell rupture . Indirect effects follow the direct effects and include vascular changes leading to ischemic necrosis, owing to the formation of thrombi and microthrombi during transient vasoconstriction . This is complemented by formation of anti‐tumor antibodies followed by phagocytosis mediated by B cells, activation of Natural Killer cells and a cytotoxic T cell mediated immune response .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other direct effects include degradation and inhibition of enzymes, protein damage, and the formation of cellular vacuoles leading to cell rupture . Indirect effects follow the direct effects and include vascular changes leading to ischemic necrosis, owing to the formation of thrombi and microthrombi during transient vasoconstriction . This is complemented by formation of anti‐tumor antibodies followed by phagocytosis mediated by B cells, activation of Natural Killer cells and a cytotoxic T cell mediated immune response .…”
Section: Discussionmentioning
confidence: 99%
“…5,9 Indirect effects follow the direct effects and include vascular changes leading to ischemic necrosis, owing to the formation of thrombi and microthrombi during transient vasoconstriction. 7,9,15 This is complemented by formation of anti-tumor antibodies followed by phagocytosis mediated by B cells, activation of Natural Killer cells and a cytotoxic T cell mediated immune response. 16,17 Moreover, it has recently been demonstrated that apoptosis is instrumental in indirect cellular injury targeting cells at the periphery of the lesion, through mitochondrial damage which causes an activation of the caspase pathway.…”
Section: Discussionmentioning
confidence: 99%
“…A case series of loco-regional cutaneous metastasis of melanoma combination therapy of cryosurgery and imiquimod was found to be successful [18]. Cryotherapy as a useful procedure used for other dermatological indications in case series and case reports mentioned in the literature are Xanthelasma palpebrarum, dermatofibrosarcoma protuberans, Refractory cutaneous Rosa Dorfman disease, cutaneous sporotrichosis, and also in oral lesions in children [19][20].…”
Section: Discussionmentioning
confidence: 99%
“…This treatment has certain advantages over surgery mainly in children. The technique is easily performed, effective, painless, requires no expensive supplies or injectable anesthesia, patients do not have to return for suture removal and it is better tolerated by fearful children [10][11][12][13][14][15][16] .These are the major advantages in Pediatric Dentistry. Surgical excision and sutures can make children and parents anxious.…”
Section: Discussionmentioning
confidence: 99%